Community multiculturalism and self-reported immigrant crime: Testing three theoretical mechanisms - Leerkes, Arjen (European journal of criminology, 2025)
There are considerable contextual differences, both between countries and municipalities, in the degree to which first- and second-generation immigrants are involved in crime. This study aims to understand such variation better, focusing on the local level. It examines whether municipal variation in self-reported crimes among Turkish- and Moroccan-Dutch men residing in 30 representative Dutch cities (n?=?902), including the four largest cities, is associated with municipal variation in multicultural attitudes, or ?community multiculturalism? (CM), among the native-Dutch living in these municipalities (n?=?2556). We propose and test a mechanism-based theoretical model that links Berry's acculturation theory to general strain theory, social bonding theory, and collective efficacy theory. In line with a previous study using police data, the self-reported offending incidence is indeed considerably lower in municipalities with higher CM levels than in other, demographically comparable municipalities. The empirical evidence suggests that the association between CM and immigrant crime is caused by CM promoting social control in the immigrant group, both at the individual and community levels.